Immunotherapeutic potential of oncolytic H-1 parvovirus: hints of glioblastoma microenvironment conversion towards immunogenicity - Angelova, Assia L.; Geletneky, Karsten; Unterberg, Andreas (Viruses, 2017)
Glioblastoma, one of the most aggressive primary brain tumors, is characterized by highly immunosuppressive microenvironment. This contributes to glioblastoma resistance to standard treatment modalities and allows tumor growth and recurrence. Several immune-targeted approaches have been recently developed and are currently under preclinical and clinical investigation. Oncolytic viruses, including the autonomous protoparvovirus H-1 (H-1PV), show great promise as novel immunotherapeutic tools. In a first phase I/IIa clinical trial (ParvOryx01), H-1PV was safe and well tolerated when locally or systemically administered to recurrent glioblastoma patients. The virus was able to cross the blood-brain (tumor) barrier after intravenous infusion. Importantly, H-1PV treatment of glioblastoma patients was associated with immunogenic changes in the tumor microenvironment. Tumor infiltration with activated cytotoxic T cells, induction of cathepsin B and inducible nitric oxide (NO) synthase (iNOS) expression in tumor-associated microglia/macrophages (TAM), and accumulation of activated TAM in cluster of differentiation (CD) 40 ligand (CD40L)-positive glioblastoma regions was detected. These are the first-in-human observations of H-1PV capacity to switch the immunosuppressed tumor microenvironment towards immunogenicity. Based on this pilot study, we present a tentative model of H-1PV-mediated modulation of glioblastoma microenvironment and propose a combinatorial therapeutic approach taking advantage of H-1PV-induced microglia/macrophage activation for further (pre)clinical testing.